2022
DOI: 10.1002/pol.20220592
|View full text |Cite
|
Sign up to set email alerts
|

Achieving ultra‐high molecular weight polyethylenes by vanadium aroylhydrazine‐arylolates

Abstract: A series of vanadium(V) aroylhydrazine-arylolates is employed in ethylene polymerization to produce ultra-high molecular weight polyethylene (UHMWPE), surprisingly extending to such coupling reactions beyond their common usage in the oxidation of hexanes and alcohols. Activated by either MAO or DMAC, the complexes V1-V3 efficiently catalyze the polymerization of ethylene into UHMWPE, that is, with an activity up to 3.37 Â 10 6 g mol À1 h À1 (60 C) and the polyethylene obtained has a molecular weight around 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Some promising results have been achieved by combining such chelates with the metal vanadium, which is the 20th most abundant metal in the Earth's crust. In particular, we and others have found that very high catalytic activities and thermally robust systems are accessible for α-olefin polymerization when conducted in the presence of co-catalysts such as dimethylaluminium chloride and the re-activator ethyl trichloroacetate [19][20][21][22][23][24][25][26][27][28][29][30][31], as well as ethylene copolymerization with the likes of propylene, 1-hexene or norbonene [32][33][34][35][36][37][38][39][40][41]. Moreover, a number of vanadyl-containing systems have shown promise in the ROP of cyclic esters [42,43], whilst other systems have been shown to be promising for both ROP and α-olefin polymerization [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 98%
“…Some promising results have been achieved by combining such chelates with the metal vanadium, which is the 20th most abundant metal in the Earth's crust. In particular, we and others have found that very high catalytic activities and thermally robust systems are accessible for α-olefin polymerization when conducted in the presence of co-catalysts such as dimethylaluminium chloride and the re-activator ethyl trichloroacetate [19][20][21][22][23][24][25][26][27][28][29][30][31], as well as ethylene copolymerization with the likes of propylene, 1-hexene or norbonene [32][33][34][35][36][37][38][39][40][41]. Moreover, a number of vanadyl-containing systems have shown promise in the ROP of cyclic esters [42,43], whilst other systems have been shown to be promising for both ROP and α-olefin polymerization [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 98%